Descriptive Epidemiological Study of Pulmonary Tuberculosis Incidence in Sampara Public Health Center, Konawe Regency, Southeast Sulawesi - Devi Savitri Effendy; Zaskia Putri Rahmadani; Sitti Syaqinah Rahmatiah MZ; Waode Siti Nur Aisyah Cahyani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Tuberculosis (TB) remains a major public health challenge in Indonesia, causing more than 100.000 deaths annually. Despite ongoing control efforts, the treatment success rate in several regions remains below the national target. In 2023, Kolaka Regency, which borders Konawe Regency, reported more than 800 TB cases with a treatment success rate of 85%, lower than the national target of 90%. During the period 2021–2025, the Sampara Community Health Center recorded 42 confirmed TB cases, highlighting the continued burden of the disease in the area. Objective: This study aimed to describe the epidemiological characteristics of pulmonary tuberculosis cases in the working area of the Sampara Community Health Center, Konawe Regency, Southeast Sulawesi, Indonesia. Methods: A descriptive study was conducted using secondary data obtained from tuberculosis records at the Sampara Community Health Center. A total of 42 pulmonary tuberculosis patients were included in the study through purposive sampling. Data were analyzed descriptively to characterize patients according to demographic, clinical, diagnostic, treatment, and geographical variables. Results: The majority of tuberculosis patients were male (66.7%), and the most affected age group was 51–60 years (31.0%). Most cases were classified as new cases (66.7%) and were bacteriologically confirmed (66.7%). Pulmonary involvement was observed in 95.2% of patients. All patients received Category 1 anti-tuberculosis drug (OAT) therapy. The most common treatment outcome was treatment completion (54.8%). HIV status was unknown in the majority of patients (81.0%), while positive chest radiography findings were reported in 59.5% of cases. Geographically, TB cases were distributed across nearly all villages within the health center’s service area, with the highest proportion reported in Andepali Village (14.3%). Conclusion: Pulmonary tuberculosis remains widely distributed in the Sampara Community Health Center service area, predominantly affecting middle-aged and older adult males. The high proportion of new and bacteriologically confirmed cases underscores the need for strengthened surveillance, early case detection, improved HIV testing coverage, and enhanced treatment adherence strategies to achieve better tuberculosis control outcomes. Keywords: Tuberculosis; Pulmonary Tuberculosis; Epidemiology; Antitubercular Agents; HIV Infection; Community Health Center